The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.ejcts.2007.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vein graft use on postoperative 1-year results after off-pump coronary artery bypass surgery

Abstract: Objective: We studied the postoperative 1-year results after off-pump coronary artery bypass surgery (OPCAB) with one or more saphenous vein grafts. Methods: We compared the clinical and angiographic results of 833 patients who underwent OPCAB between 1998 and 2004. Group 1 patients (n = 135) received one or more vein grafts. Group 2 patients (n = 698) received total arterial grafts. Coronary angiographies were performed early postoperatively (n = 804, 1.6 AE 1.5 days), and 1 year postoperatively (n = 671, 12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…Only a few studies conducted in a small number of patients have reported results of CABG using SV composite grafts, and this graft configuration is controversial [6-8,14]. The SV graft may be regarded as a major ITA collateral branch whose caliber is significantly larger than that of the main artery itself.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies conducted in a small number of patients have reported results of CABG using SV composite grafts, and this graft configuration is controversial [6-8,14]. The SV graft may be regarded as a major ITA collateral branch whose caliber is significantly larger than that of the main artery itself.…”
Section: Discussionmentioning
confidence: 99%
“…A significantly lowered patency for saphenous vein grafts relative to ITA grafts has been suggested to result from the type of graft, presence of dyslipidemia, exposure and quality of stabilization, and increased procoagulatory activity in OPCAB patients. 10,15,16 A previous study that used early postoperative angiography 17 demonstrated an overall graft patency rate among patients who received venous grafts significantly lower than that among patients who received total arterial grafts. Multivariable logistic regression analysis failed to demonstrate early experience as an independent predictor, and venous graft use itself was an independent predictor of graft failure during the first postoperative year after OPCAB.…”
Section: Discussionmentioning
confidence: 99%
“…Although prospective randomized trials carried in the hands of surgeon with high level of expertise have shown that early patency and adequacy of the revascularization could be equivalent between on and off-pump revascularization [83,91], meta-analyses have reported a decrease in the number of grafts with OPCAB surgery and a lower patency rate especially with vein graft [92,93]. However, recent studies tend to demonstrate similar transit-time flowmetric results, as well as comparable graft flow reserve with both techniques [94].…”
Section: Off-pump Coronary Artery Bypass Surgerymentioning
confidence: 99%